Brand attitude as the catalyst: transforming perceived ESG to consumer's purchase intention in low-carbon consumption - Zhang, Ran; Zhou, Xiaolong; Liu, Qijia; Wang, Chen (Frontiers in Psychology, 2025)
IntroductionThe purpose of this research is to examine the influence of consumers' perceptions of corporate ESG (Environmental, Social, Governance) performance on brand-related attitude and sustainable consumption behaviors, with attention to the boundary conditions imposed by varying degrees of green skepticism toward low-carbon offerings.MethodsThis study conducts a multi-wave survey design to test all hypotheses.ResultsThe empirical study establishes three critical pathways: (1) All perceived ESG dimensions exert significant positive effects on brand trust, (2) Environmental and governance indicators emerge as unique predictors of brand identification, and (3) These attitudinal shifts, in turn, positively influence consumers' intentions to purchase low-carbon products.DiscussionTheoretical contributions are twofold: First, the integration of signaling theory with brand attitude frameworks elucidates the psychological sequencing through which institutional sustainability signals translate into purchase behaviors. Second, the typological approach to green skepticism advances existing environmental psychology models by delineating context-specific moderation effects. Practically, the results provide actionable insights for marketers aiming to design effective ESG communication strategies and foster consumers' positive brand attitude in low-carbon consumption.